Zombie butts from Uranus! - Griffiths, Andy, 1961-; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 2004)
In the deepest, darkest corner of the solar system lies an enemy more terrifying than the people of Earth could imagine. Vicious warriors who will let nothing stand in the way of their crusade for galactic domination. They're cunning. They're ruthless. They're zombie butts from Uranus! Earth has only one hope for salvation. Zack, a twelve-year-old who wants nothing more than to wash his hands of the whole butt-fighting business. But Zack cannot shirk his duty--and he cannot escape his destiny. Joined by an assortment of butt-fighters, and his own brave butt, Zack will do what he must to rid the earth of these stinky space invaders.
"Sequel to 'The day my butt went psycho!'"--Cover.
Keywords: Buttocks -- Juvenile fiction; Children's stories; Science fiction; Humorous fiction